The U.S. Demographic Transition - Greenwood, Jeremy; Seshadri, Ananth (American Economic Review, 2002)
Between 1800 and 1940 the U.S. went through a dramatic demographic transition. In 1800 the average woman had 7 children, and 94 percent of the population lived in rural areas. By 1940 the average woman birthed just 2 kids, and only 43 percent of populace lived in the country. The question is: What accounted for this shift in the demographic landscape? The answer given here is that technological progress in agriculture and manufacturing explains these facts.